1993
DOI: 10.1101/gad.7.12a.2378
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Rb-related p130 through its interaction with CDK2 and cyclins.

Abstract: A two-hybrid protein interaction screen was used to isolate cDNAs encoding human proteins that can interact with human CDK2 in yeast. A new member of the retinoblastoma susceptibility gene family, Rbr-2 (Rb-related), was obtained. The sequence of the Rbr-2 protein shares -50% identity with p107 and homology to Rb within the pocket domain. Several lines of evidence indicate that Rbr-2 is the adenovirus E1A-associated p130. Like Rb and p107, p130 Rbr-2 can bind to viral oncoproteins, SV40 large T antigen, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
355
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 452 publications
(363 citation statements)
references
References 58 publications
(66 reference statements)
7
355
1
Order By: Relevance
“…RB is the founder of the RB family of genes and proteins, since two other factors structurally and functionally related, namely p107 (RBL1) (Ewen et al, 1991;Zhu et al, 1993) and Rb2/p130 (RBL2) (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993), have been subsequently identified. The RB family proteins share a considerable structural homology, primarily at the level of the 'pocket' domain, a complex structure subdivided in A-domain, spacer and B-domain.…”
Section: And References Therein)mentioning
confidence: 99%
See 2 more Smart Citations
“…RB is the founder of the RB family of genes and proteins, since two other factors structurally and functionally related, namely p107 (RBL1) (Ewen et al, 1991;Zhu et al, 1993) and Rb2/p130 (RBL2) (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993), have been subsequently identified. The RB family proteins share a considerable structural homology, primarily at the level of the 'pocket' domain, a complex structure subdivided in A-domain, spacer and B-domain.…”
Section: And References Therein)mentioning
confidence: 99%
“…The subsequent characterization of these proteins first identified p105 as the product of the RB gene (Whyte et al, 1988), and then p60 as cyclin A (Giordano et al, 1989;Pines and Hunter, 1990). Later, genes encoding p107 (Ewen et al, 1991;Zhu et al, 1993) and pRb2/p130 (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993) were cloned using different strategies. Finally p300, together with CBP, defines a family of transcriptional adaptor proteins that are specifically targeted by the E1A oncoprotein (Arany et al, 1995).…”
Section: And References Therein)mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular cloning of the p107 cellular protein that forms specific complexes with E1A and large T-antigen revealed that it possessed significant homology to pRb (Ewen et al, 1991). Similarly, the p130 cellular protein, which binds to viral oncoproteins, has been cloned and is also sometimes referred to as pRb2 (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993; see also Genovese et al, in this issue).…”
Section: The Retinoblastoma Family Of Proteinsmentioning
confidence: 98%
“…Interaction involves the same 10 amino-acid LXCXE domain that is involved in pRb binding. Similarly, the p130 cellular protein, pRb2 binds to large T-antigen (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993). Mutations in the 10 amino-acid LXCXE domain abrogate p107 and pRb2/p130 binding as well as pRb.…”
Section: Interaction Of Sv40 Large T-antigen With Prb and Its Family mentioning
confidence: 99%